Efektivitas Lama Perendaman Ekstrak Bawang Putih dan Pemberian Pupuk Cangkang Kerang terhadap Pertumbuhan Stek Tanaman Mawar (Rosa Hybrida L.) - Utomo Relmana Tarigan; Najla Lubis; Desi Sri Pasca Sari Sembiring (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effectiveness of the duration of soaking garlic extract and the provision of shell fertilizer on the growth of rose plant cuttings (Rosa hybrida L). This study used a Factorial Randomized Block Design (RAK) method consisting of 2 factors with 48 plots, namely: The first factor is the duration of soaking garlic extract given the symbol